Temporal features of the development of the cities of the Kharkov region - Kateryna Kravchenko (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
Kharkiv region is one of the most developed regions of Ukraine. One of the main problems is the slowness of the territorial development of the population settlement system, the excessive concentration of population in the city of Kharkiv. The transition from monocentric to polycentric model of spatial regional development of the Kharkiv region is one of the priority directions of development. The practical realization of this task depends on the knowledge of the laws of the population movement of the cities of Kharkiv region. Analysis of the dynamics of the population of cities in the Kharkiv region and the population growth rate from 1992 to 2016 allowed grouping the cities of the region at the rate of population decline due to their population size.